Development management model of elite athletes in team sports games - Trninić, Marko; Trninić, Slavko; Papić, Vladan (2009)
Abstract: The scientific and expert approach to defining a model of managing the development of top-level athletes in team sports games is oriented toward the challenging values that mark a certain position and role in a team sports game. A hypothetical dynamic model of development management of top-level athletes in team sports games, which explicitly shows the order of procedures in the process of multidimensional development of athletes using the concepts of the dynamic systems theory has been suggested. The hypothetical model of management shows that the athlete’s development is primarily under the influence of genetic potential, sports preparation process and the competition format, as well as the management of their lifestyle. In the process, the athlete’s development is seen as a dynamic and plastic process under the influence of selective procedures and training programs that enable a continuous change in the level of the athlete’s performance and sports preparation
Bibliografija: 40 jed.
Sažetak
Keywords: Timski sportovi -- Ekipni sportovi -- Vrhunski sportaši -- Životni stil -- Sportska priprema -- Izvedba -- Trening -- Teorija dinamičkih sustava